An Empirical Study on the Use of Justice for Implicated Offenders — Targeting 117 Criminal Judgments - Zeju Zhou; Qiwei Zhang (Law and Economy, 2024)
In China’s criminal law theory, implicated offenders are defined as “a crime to be punished”, and unless otherwise provided for in the criminal law, they are to be punished as “a felony”. In judicial practice, the number of implicated cases is increasing, and there are many controversial points. The first is the contradiction at the theoretical level, because it has become a trend in traditional civil law countries to abolish implicated offenders, and the controversy over the existence and abolition of implicated offenders is constantly controversial in legal theory. The second is the contradiction at the practical level, in terms of the application of specific cases, the existing legal provisions of the implicated offender cannot exhaust the current practical needs, and there is no clear and comprehensive legal basis for determining the implicated offender.